Efektivitas Penerapan Pelayanan Publik Berbasis Online di Masa Pandemi Covid-19 Pada Dinas Kependudukan Dan Pencatatan Sipil Kota Samarinda - Lilis Hariyana; Anwar Alaydrus; Iman Surya (Jurnal Ilmu Pemerintahan, 2022)
This type of research is descriptive qualitative. The data collection techniques used were purposive sampling and accidental sampling. This study aims to analyze and describe the effectiveness of implementing online-based public services during the Covid-19 pandemic at the Samarinda City Population and Civil Registry Service. The results of this study indicate that through the implementation of online services, Disdukcapil has made every effort to continue providing services in the midst of the Covid-19 pandemic, but the implementation of online services at Disdukcapil has not been fully effective. The requirements file is not fully complete and fulfills the requirements. Procedurally, there are people who are still having problems in the process of uploading files to the website due to a lack of understanding and supporting facilities. The service time has been adjusted to the Disdukcapil Service Operational Standards (SOP) and all types of services other than certificates can be completed in minutes. Fees for all types of services are free. Service products have increased since online services during the pandemic and complaints services are still considered slow by the public. The supporting factors in carrying out online services are the adequacy of Human Resources (HR) at Disdukcapil and the availability of supporting devices. Then the inhibiting factors in this online service are network disturbances and the level of public understanding that is still lacking about online services.